Pengaruh Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Smartphone Infinix Pada Marketplace Shopee di Masyarakat Kelurahan Isola Bandung - Siti Rahmayati; Dahlan Ramdhani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to determine the effect of price and product quality on purchasing decisions for infinix smarthphone products in Shopee e-commerce, with a case study of the Isola urban community in Bandung. The research method used is quantitative with data collection techniques through questionnaires distributed to 100 respondents. The data analysis technique used is multiple linear regression analysis. The results showed that price and price significantly influenced the decision to purchase infinix smarthphone products in Shopee e-commerce. Price makes a greater contribution than product quality in influencing purchasing decisions. This research is expected to provide benefits for e-commerce businesses in increasing competitive pricing and product quality to increase consumer purchasing decisions.